Blockchain for Secure Electronic Health Records Management - Praveen Kumar Rawat (PT. Delitekno Media Madiri, 2025)
Electronic Health Records (EHRs) are essential to modern healthcare infrastructure, yet they face persistent challenges related to data security, interoperability, and unauthorized access. Blockchain technology, through its use of cryptographic protocols, smart contracts, and consensus mechanisms, offers a decentralized and tamper-resistant solution for managing EHRs. This paper explores the potential of blockchain in addressing critical limitations of conventional EHR systems, focusing on data immutability, fine-grained access control, and real-time data synchronization. By leveraging distributed ledger technology (DLT), the proposed approach reduces single points of failure and mitigates cybersecurity vulnerabilities. Furthermore, this study discusses practical implementations and case studies that demonstrate how blockchain can enhance trust, transparency, and efficiency in health data management. The analysis reveals that a well-designed blockchain-based EHR framework can minimize data breaches, protect patient data rights, and streamline operations across healthcare institutions. The paper concludes that blockchain presents a transformative path forward for secure and interoperable EHR systems. Future research should aim to refine architectural models, address scalability constraints, and ensure compliance with healthcare regulations and standards such as HIPAA and GDPR to facilitate real-world adoption and sustainable deployment.